Lepra reactions: a study of 130 cases from Pakistan - Saadia Tabassum; Mutaher Zia; Adeel Akbar Khoja; Juliet David; Muhammad Iqbal; Muhammad Junaid (Journal of the Pakistan Medical Association, 2021)
Objective: To determine the occurrence and characteristics of lepra reactions, in patients at a leprosy hospital, in Pakistan. Methods: A retrospective study was conducted on patients admitted at Marie Adelaide Leprosy Centre (from January 1, 2013 to December 31, 2015) for management of lepra reactions. The data was used after approval from MALC management. Results: Lepra reactions, an immunological complication of leprosy can occur before, during or after treatment. The study included 130 cases. Mean age at onset of the first episode was 39 years. Male-female ratio was 2.7:1. Borderline lepromatous was the most common classification (58%). 58% cases had the first episode of a type 1 reaction and 42% had type 2. 44% presented with a reaction at diagnosis. 38% had it during and 18%, after discharge from treatment. Type 1 was frequent at diagnosis and during treatment. Type 2 was common after discharge.Risk factors associated with recurrence were skin lesions, fever, lymphadenopathy and type of reaction. Inflamed plaques were most common in type 1 and crops of erythematous nodules in type 2. Ulnar was the most common enlarged nerve (80%). Conclusion: It is important that health care providers are aware of the clinical manifestations of lepra reactions, to diagnose them early; thus preventing deformity and disability. Keywords: Leprosy, Lepra reactions, Type 1 (reversal reactions), Erythema Nodosum Leprosum (ENL), Peripheral Neuropathy, Neuritis. Continuous...